An-Naẓrah an-Naqdiyyah ʿinda al-Imām asy-Syāṭibī fī Bināʾ Fiʿl al-Amr wa Ḥukm al-Fiʿl al-Muḍāriʿ maʿa Nūn at-Tawkīd al-Mubāsyirah wa Nūn an-Niswah - Zaenal Abidin; Ishomuddin Ahmad; Maskanah Alfiqhiyyah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
The eighth century of the Hijri era witnessed the emergence of a prominent scholarly figure in Arabic grammar, namely Imam al-Shāṭibī (may Allah have mercy on him). He was distinguished among the grammarians of his time by his independent approach to grammatical research and the verification of grammatical issues. He authored a work on Arabic grammar and morphology entitled Al-Maqāṣid al-Shāfiyah fī Sharḥ al-Alfiyyah li Ibn Mālik. This study aims to clarify Imam al-Shāṭibī’s critical perspective on the construction of the imperative verb (fiʿl al-amr) and the grammatical ruling of the present tense verb (fiʿl al-muḍāriʿ) when accompanied by the direct emphatic nūn (Nūn al-Tawkīd al-Mubāsyirah) and the feminine nūn (Nūn al-Niswah) by employing the analytical method. The study compares the opinions of scholars regarding these grammatical issues based on classical works of grammar, morphology, linguistics, and rhetoric, while evaluating and giving preference to the strongest opinions. The study finds that scholars have expressed various views on these issues. Imam al-Shāṭibī maintained that the imperative verb is built on sukūn (quiescence) unless it is a defective verb (muʿtall), presenting both criticism and refutation of the numerous opposing opinions. The study concludes that his view is the strongest because of the soundness of its evidence and its ability to withstand counterarguments.